Health economic evaluation alongside randomised clinical trial of a health behaviour intervention to manage type 2 diabetes in Nepal - Padam Kanta Dahal; Zanfina Ademi; Lal Rawal; Rashidul Alam Mahumud; Grish Paudel; Biraj Karmacharya; Haruka Sakamoto; Tomohiko Sugishita; Corneel Vandelanotte (Global Health Research and Policy, 2024)
Abstract Background Prevention of type 2 diabetes is becoming an urgent public health concern in low and middle-income countries (LMICs). However, there is currently no evidence of a cost-effective approach of health behaviour interventions from community settings in low-income countries like Nepal. Therefore, this study aimed to assess the within-trial economic evaluation of a health behaviour intervention compared with usual care for managing type 2 diabetes in a community setting in Nepal. Methods We randomly assigned 30 clusters comprising 481 patients with type 2 diabetes of which 15 to a health behaviour intervention (n = 238 patients) and 15 to the usual care (n = 243 patients). Patients in the intervention group received community health workers-led intensive training for diabetes self-management along with regular phone calls and ongoing support from peer supporters. Costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER) as costs per QALYs gained were assessed after 6-month from a healthcare system perspective. Probabilistic sensitivity analysis was conducted using 10,000 Monte Carlo simulations to assess the impact of uncertainty of cost-effectiveness analysis under the threshold of three times gross domestic product (GDP) per capita for Nepal (i.e., US $4,140). Results Over the 6-month, the intervention yielded an incremental cost of US $28.55 (95% CI = US $21.26 to US $35.84) per person and an incremental QALYs of 0.0085 (95% CI = -0.0106 to 0.0275) per person. The ICER associated with the health behaviour intervention was US $3,358.82 (95% CI = US $-2005.66 to US $3,974.54) per QALY gained, which was below the estimated threshold, indicating a cost-effective approach with a net monetary benefit of US $6.64 (95% CI = US $-22.62 to US $78.01). Furthermore, the probabilistic sensitivity analysis consisting of 10,000 Monte Carlo simulations indicates that the intervention being cost-effective at the given threshold was 89.63%. Conclusions Health behaviour interventions in community settings are a cost-effective approach to manage type 2 diabetes, offering good value for money. However, more studies focused on long-term follow-up across diverse setting of LMICs should be warranted to assess the maximum impact of such interventions. Trial registration Australia and New Zealand Clinical Trial Registry (ACTRN12621000531819) Registered on 6th May 2021.